Choice of second-line systemic therapy in stage IV small cell lung cancer (SCLC) – A decision-making analysis amongst European lung cancer experts. (August 2020) - Früh, M.; Panje, C.M.; Reck, M.; Blackhall, F.; Califano, R.; Cappuzzo, F.; Besse, B.; Novello, S.; Garrido, P.; Felip, E.; O'Brien, M.; Paz Ares, L.; et al.
Highlights: Second-line therapy of stage IV SCLC is heterogeneous among European experts. After 6 months from first-line treatment, 92 % recommend platinum re-challenge. 3–6 months after first-line treatment no consensus was found. In very early recurrence CAV for fit & topotecan for unfit patients was recommended. Abstract: Objectives: Stage IV small cell lung cancer (SCLC) is associated with short survival and progression after first-line systemic therapy frequently occurs within months. Although topotecan is approved for second-line treatment, its efficacy is limited, and treatment heterogeneity exists. Material and methods: The decision-making patterns for second line treatment of 13 European medical oncologists with expertise in SCLC were analyzed. Results: The two criteria most relevant to decision-making were the performance status and the interval of recurrence since first-line treatment. With an interval of less than 3 months since the end of first-line chemotherapy, 62 % of the experts recommended cyclophosphamide, doxorubicin and vincristine (CAV) for fit patients and 54 % recommended topotecan for unfit patients. For an interval of more than 6 months, a clear consensus for a re-challenge with a platinum doublet was achieved (92 %). However, there was no consensus on the second-line therapy with an interval of 3–6 months since the end of first-line therapy. Conclusion: Real world practice may differ from recommendations in general guidelines and cannot always be directly derived from trial results as other factor such as habits, patient's preference, convenience or costs have to be factored in.